The Journey Mapping Playbook A Practical Guide to Preparing, Facilitating and Unlocking the Value of Customer Journey Mapping - Angrave, Jerry (De Gruyter, 2020)
The Journey Mapping Playbook is an accessible how-to toolkit aimed at customer experience and marketing professionals looking for ways to improve customer and employee experience. Using visualisation, templates and case studies this is a practical guide to planning, facilitating and delivering a strategic, supportive and effective journey mapping workshop. The Journey Mapping Playbook is based on the author's real-world experience of running hundreds of journey mapping sessions. Understanding the priorities and pain points in customers' lives is critical to achieve business success. Helping you to nurture better and more profitable customer experiences, this book will help you to: Define journey mapping Understand why it is commercially important Prioritise which journeys to focus on and how Decide who to invite and which tools to prepare Plan for an effective session Make every stage of the journey relevant and purposeful Build an ongoing programme The Journey Mapping Playbook shows you how to understand your customers better, whatever the size or sector of your business. Jerry Angrave, Founder and CEO of Empathyce, UK.